Chemical Constituents of Caesalpinia bonduc - Thi Huyen, Le; Thu Hau, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 4, 2022)
This phytochemical investigation of Caesalpinia bonduc reported eight known compounds, namely threo -2,3-bis(4-hydroxy-3-methoxyphenyl)-3-methoxy-propanol (1) , evofolin-B (2) ,  trans -Linalool-3,6-oxide- β-D -glucopyranoside (3) , 1-(2-methylbutyryl)phloroglucinol-glucopyranoside (4) , 1-(3 methylbutyryl)phloroglucinol-glucopyranoside (5) , (+)-isolariciresinol (6) , protocatechuic acid (7) , methyl gallate (8) . The structures of these compounds were identified by 1D- and 2D- nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) and by comparison with those reported in the literature. Compound 2 exhibited significant cytotoxic effects against the HepG2 cell line with an IC 50 value of 48.37±3.18 µ M.